Impact of Eutectic Solvents Utilization in the Microwave Assisted Extraction of Proanthocyanidins from Grape Pomace - Rodrigo T. Neto; Sónia A. O. Santos; Joana Oliveira; Armando J. D. Silvestre (Molecules, 2021)
The extraction of proanthocyanidins (PACs), despite being an important and limiting aspect of their industrial application, is still largely unexplored. Herein, the possibility of combining eutectic solvents (ESs) with microwave assisted extraction (MAE) in the extraction of PACs from grape pomace (GP) is explored, aiming to improve not only the extraction yield but also the mean degree of polymerization (mDP). The combination of choline chloride with lactic acid was shown to be the most effective combination for PACs extraction yield (135 mgPAC/gGP) and, despite the occurrence of some depolymerization, also enabled us to achieve the highest mDP (7.13). Additionally, the combination with MAE enabled the process to be completed in 3.56 min, resulting in a considerably reduced extraction time.